A Case Report of Intrauterine Device Migration: Uterine Penetration and Bladder Involvement with Secondary Stones 3 Years Post-Insertion - Chen Z; Lv Z; Shi Y (Dove Medical Press, 2024)
ZhiLong Chen, Zhong Lv, YunFeng Shi Department of Urology, Wujin People's Hospital, Changzhou Medical Center, Nanjing Medical University, Changzhou, Jiangsu, 213100, People's Republic of ChinaCorrespondence: Zhong Lv, Department of Urology, Changzhou Wujin People's Hospital, Changzhou Medical Center, Nanjing Medical University, Changzhou, Jiangsu, 213017, People's Republic of China, Tel +86-13584328748, Email lzabc0105@163.comBackground: Intrauterine devices (IUDs) are among the most popular contraceptive methods globally due to their convenience and cost-effectiveness. However, improper placement can lead to complications such as device migration and uterine perforation, with increased risk observed when IUDs are implanted within four to six weeks postpartum. Typically, patients are asymptomatic or experience mild lower abdominal discomfort or minor abnormal vaginal bleeding following IUD displacement. Advances in diagnostic techniques have resulted in an increased reporting of uterine perforations due to IUD migration. Although rare, secondary stone formation following IUD perforation has been noted. In 2023, cases of IUD perforation were reported in women with a history of multiple cesarean sections and in a young woman without detailed marital history.Prior Presentation: The 43-year-old patient, who had an IUD inserted three years prior, exhibited symptoms of frequent urination and painful urination unrelieved by anti-infective and analgesic treatments. The patient underwent cystotomy for foreign body removal, which revealed the IUD had perforated the uterus and bladder, with both arms of the device invaded into bladder wall and covered with concentric stone layers. Complete removal of the IUD and surrounding stones, followed by suturing and postoperative anti-infection analgesic treatment, led to significant symptom improvement.Conclusion: This case underscores the importance of regular IUD check-ups to prevent uterine perforation and the necessity of considering IUD migration in patients presenting with lower urinary tract symptoms without routine IUD examination. While self-examination by the patient through the strings in the vagina is possible, imaging studies are also indispensable. Surgery has proven to be an effective solution for such complications, but cystoscopy is not always the best option, and the decision to perform open surgery should be based on the patient's perforation and the condition of the surrounding tissues. This paper emphasizes the need for vigilance and proper clinical management.Keywords: IUD, migration, bladder stone, cystoscopy, computed tomography